The Influence of Empowerment, Work Motivation, and Physical Work Environment on Turnover Intention with Organizational Commitment as an Intervening Variable in Teachers of the Yayasan Perguruan Rakyat Jakarta - Izma Nurhanifah Fauzi; Suryono Effendi (Budapest International Research and Critics University, 2023)
This study aims to determine and analyze the effect of empowerment, work motivation, physical work environment on Turnover Intention through organizational commitment as an intervening variable at the Jakarta People's College Foundation. The research sample was 100 teachers. Data collection using SEM AMOS is used as an analysis technique. The results of this study indicate that Empowerment has a positive and significant effect on organizational commitment, Work motivation has a positive and significant effect on organizational commitment, Physical work environment has a positive and significant effect on organizational commitment, Empowerment has a negative and significant effect on Turnover intention, Work motivation has a negative and significant effect on Turnover intention, Physical work environment has a negative effect on Turnover Intention, Organizational commitment has a negative effect on Turnover Intention, Empowerment has no significant effect on Turnover intention through organizational commitment, work motivation has a significant effect on Turnover intention through organizational commitment, physical work environment has a significant effect on Turnover intention through organizational commitment.